Penanaman Nilai Karakter dan Moral Mahasiswa Melalui Mata Kuliah Anak Berkebutuhan Khusus dan Pendidikan Inklusi - Bayu Pamungkas (Universitas PGRI Kanjuruhan Malang, 2018)
This study aims to determine the planting of character and moral values of students through the subjects of Children with Special Needs and Inclusion Education students of the PGSD FKIP UPY study program. The research design uses a qualitative approach and the method used is a case study. Participants in this study were seventh semester students in the subjects of Children with Special Needs and Inclusive Education of PGSD FKIP UPY study program. Data collection techniques using observation, interviews, documentation. Test the validity of the data by extension of observation and triangulation. Data processing and analysis techniques use interactive cycle process analysis consisting of data reduction, data presentation, and data verification. The results of this study are that there are several character and moral values that can be embedded in the subjects of Children with Special Needs and Inclusive Education, among others: tolerance, nationalism, friendship / communicative, social care and responsibility.